Evaluation of the implementation of the government's internal control system in managing village finances in Bulawan Village - Raranta, Audy; Rundengan, Fanda D. P. (Yayasan Widyantara Nawasena Raharja, 2025)
The implementation of the Government Internal Control System (SPIP) plays a crucial role in ensuring transparency, accountability, and effectiveness in managing village finances. This study aims to evaluate how SPIP is applied in the areas of monitoring and financial administration in Bulawan Village, based on Government Regulation No. 60 of 2008 and the Ministry of Home Affairs Regulation No. 20 of 2018. Using a qualitative descriptive approach, data were collected through interviews, direct observations, and documentation. The findings reveal that the internal control system in Bulawan Village has generally been implemented in accordance with existing regulations. Continuous monitoring is carried out regularly by village officials and supervisors, ensuring compliance with financial management standards. However, several weaknesses were identified, particularly in the areas of independent evaluations and follow-up actions on audit recommendations. These shortcomings are mainly due to limited human resources and the lack of structured internal audit mechanisms at the village level. This study contributes empirically by providing in-depth insights into how SPIP functions within the unique context of local village governance in Indonesia. It emphasizes the importance of strengthening monitoring mechanisms, enhancing staff capacity, and integrating digital systems to improve accountability and financial reporting. The results can serve as a reference for policymakers and local governments in developing more effective internal control frameworks for rural financial management.